SUSCEPTIBILITY PATTERN OF PSEUDOMONAS AERUGINOSA PRODUCING ENZYMES AGAINST ANTIMICROBIAL AGENT CELL FREE SUPERNATANT OF LACTOCOCCUS WITH THE FOCUS ON ITS DETERMINING QUANTITATIVELY BY OD (ENZYME LINKED IMMUNE SORBENT ASSAY) - Mohsin, Yusra Mb; Majeed, Huda Zuheir; Hasan, Ali Murtatha; Bataah, Enaam Hamed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The present work was conducted to explore the prevalence of Pseudomonas aeruginosa that produce lipase and protease enzymes in 40 samples, as well as detection of quality and quantity production and determine its susceptibility to antimicrobial. Methods: The antimicrobial activity of Lactococcus cell free supernatant (CFS) on P. aeruginosa growth and quantity production of enzymes by two methods (special media and OD) were also studied. Results: A total of 8(20%) and 13(32%) isolates were found to be positive to P. aeruginosa producing lipase and protease, respectively. The in vitro antimicrobial activity results revealed that all isolates producing enzymes showed sensitive to CFS of Lactococcus, only one isolate exhibited low sensitivity to CFS 4 mm, however, these isolates varied in their sensitivity to CFS ranged 4-15 mm. Conclusion: Results of the quantity production of P. aeruginosa enzymes with CFS of Lactococcus showed and exerts growth inhibitory activity and reduce the production of enzymes. We could be concluded that CFS of Lactococcus has great potential antimicrobial activity against P. aeruginosa growth and its ability on enzymes production. Keywords: Pseudomonas aeruginosa, Lactococcus, Cell-free supernatant, Optical density, Lipase, Protease.